RESOURCE-BASED THEORY (RBT) MODEL IN IMPROVING EMPLOYEE PERFORMANCE: INCLUSIVE LEADERSHIP AND SELF-EFFICACY APPROACH - Yanti Musyawarah; Nuzuliati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to explore the application of Resource-Based Theory (RBT) in improving employee performance through an inclusive leadership and self-efficacy approach. Based on RBT, an organization's internal resources, including leadership and individual self-confidence, are strategic assets that can provide competitive advantage. An inclusive leadership approach is seen as being able to create a work environment that supports diversity, collaboration, and innovation, thereby strengthening employee ownership and motivation. In addition, employee self-efficacy, which is the belief in their ability to achieve work goals, is an important factor in maximizing individual potential. This study uses a quantitative method with a survey of employees in various industrial sectors. The results show that inclusive leadership significantly increases self-efficacy, which ultimately has a positive impact on employee performance. These findings provide theoretical and practical contributions, especially in human resource management, by emphasizing the importance of inclusive leadership and self-efficacy development to optimize organizational performance. This study also recommends strategies that can be implemented by managers in building an inclusive work culture to achieve sustainable competitive advantage.